EFEKTIVITAS GAME BASED LEARNING BERBANTUAN FLASHCARD TERHADAP PEMAHAMAN KONSEP MATEMATIKA - Nike Marsita, Endah; Rahmawati, Dwi; Gunawan, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning is a fundamental component as it develops logical and analytical thinking, as well as conceptual understanding that underpins other fields of study. However, the mathematical conceptual understanding of second-grade students at MI Muhammadiyah Hadimulyo remains low, and instruction is still dominated by conventional approaches. This issue needs to be addressed through the implementation of Game Based Learning supported by Flashcards. This study aims to examine difference in mathematical conceptual understanding between Game Based Learning assisted by Flashcards and conventional learning. It employs a quasi-experimental approach using a cluster random sampling method. The population included all second-grade students, while the sample consisted of classes IIA and IID of MI Muhammadiyah Hadimulyo, where IIA applied conventional learning and IID applied Game Based Learning assisted by Flashcards. The instruments used were an observation sheet and a mathematical conceptual understanding test. The data were analyzed using a two-way ANOVA with a significance level of 0,05. The findings indicate that Game Based Learning assisted by Flashcards had a significant effect and was effective in improving second grade students’ understanding of mathematical concepts at MI Muhammadiyah Hadimulyo.